Feasibility Analysis of Regular Gas Station Development Projects in Relation to the Economy - Rediansyah, Trisna Ferdy; Andono, Agung Ari; Farhan, Ohan; Anwar, Saihul (Indonesian Journal of Advanced Research, 2025)
This study analyzes the feasibility of the construction of regular petrol stations in Sepaku District, North Penajam Paser Regency, East Kalimantan. The need for development arises due to the increase in the number of vehicles that is not proportional to the availability of fuel infrastructure. A quantitative approach is used through fuel demand analysis, RAB preparation, and economic evaluation with NPV, BCR, and Payback Period. The results show that Semoi Dua Village is strategic because it is on the path to IKN with high population growth. Fuel needs are estimated at ±311,000 liters per week. The project is economically feasible with a positive NPV of IDR 15 billion, a BCR of 1.3, and a payback period of four years. Petrol stations are considered prospective operationally and economically.